Revitalisasi Peran Pesantren: Program Entrepreneurship dalam Mengembangkan Minat Bakat Santripreneur di Pondok Pesantren (Studi pada Pondok Pesantren Miftahul Mubtadi’in Ar-Ridho Krempyang) - Nizar Khiftirus Sunah, M.; El Muna, Naily (Journal of Islamic Economics Studies and Practices, 2024)
Miftahul Mubtadiin Ar-Ridho Nganjuk Islamic Boarding School is one of the Islamic Boarding Schools in the city of Nganjuk that implements an entrepreneurship program for its students. One of the entrepreneurship programs implemented at the miftahul mubtadi'in Islamic boarding school is Agriculture, Animal Husbandry and Tempeh Tofu Industry. This study aims to find out the role of the Miftahul Mubtadiin Ar-Ridho Islamic Boarding School in fostering the interest and talent of preneur students in the boarding school and to find out the activities of preneur students carried out at the Miftahul Mubtadiin Ar-Ridho Islamic Boarding School in fostering the interest and talent of preneur students. The method used in this study is descriptive qualitative research. The data collection technique in this study uses interview, observation, and documentation study techniques. The result of this research is the role of the Miftahul Mubtadiin Ar-Ridho Islamic Boarding School in developing the talent interests of students, namely to accommodate and grow the talents of students, become consumers and become decision-makers so that the entrepreneurial activities run well. And Islamic boarding schools also play a role in providing facilities such as special buildings as a place for activities, providing capital so that these activities can run well, then collaborating with several business partners such as local farmers and alumni.